1973
DOI: 10.1001/archpedi.1973.02110190134004
|View full text |Cite
|
Sign up to set email alerts
|

Enteritis Due to "Related Vibrio" in Children

Abstract: A "related Vibrio" was found in numerous stool cultures from a 16-month-old boy with chronic diarrhea. An outbreak of acute diarrhea occurred in the nursery frequented by this boy; the same Vibrio was isolated in the stool cultures of all symptomatic cases. Using a new device, the related Vibrio has also been isolated in intestinal aspirates at different levels of the gastrointestinal tract in several cases.Slight changes were observed in the jejunal mucosa of the child with chronic diarrhea.Infecti on of catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…Other studies (7,16) have shown that isolates from chickens, swine, sheep, dogs, and cows were identical serologically with strains isolated from human patients. Serogroups 14,15,and 22, presently found only among human isolates, are consistent with person-to-person spread reported by some workers (7,10,19). Recently, Blaser et al 5have brought additional evidence of person-toperson transmission of C. jejuni.…”
Section: _0supporting
confidence: 91%
“…Other studies (7,16) have shown that isolates from chickens, swine, sheep, dogs, and cows were identical serologically with strains isolated from human patients. Serogroups 14,15,and 22, presently found only among human isolates, are consistent with person-to-person spread reported by some workers (7,10,19). Recently, Blaser et al 5have brought additional evidence of person-toperson transmission of C. jejuni.…”
Section: _0supporting
confidence: 91%
“…was believed to be limited to the small bowel (Skirrow, 1977) though detailed pathology is scanty. The literature contains two necropsy reports describing a haemorrhagic jejunitis (Wheeler and Borchers, 1961;Evans and Dadswell, 1967) and a description of minor changes in a jejunal biopsy (Cadranel et al, 1973). In the latter case, however, Giardia lamblia was also isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Early in the 20 th century researchers investigating veterinary cases of foetal abortion and winter dysentery in cattle [7] described several species that would later become part of the Campylobacter genus, including Vibrio jejuni [8] , V. fetus [9] , V. fetus venerealis and V. fetus intestinalis [10]. Isolation techniques that permitted the growth of Campylobacter from human faeces drew attention to its importance as a human pathogen [1113]. The genus name Campylobacter (meaning curved rod) was proposed by Sebald and Véron in 1963 and subsequently verified in 1973 with the broader acceptance of Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%